A sweltering afternoon: Herberton, Far North Queensland - Tass Holmes (eTropic: electronic journal of studies in the tropics, 2019)
This short prose comprises childhood recollections interspersed with a brief contemporary travel ‘memoir’, juxtaposing past and present narratives in a limited gothic style. It conveys a sense of the sultry ambience of far north Queensland’s tablelands region, inland from Cairns, with a particular focus on Herberton, a town in the ‘dry tropics’, with a mining history.